STUDI ALTERNATIF PERENCANAAN DENGAN METODE KOMPOSIT GEDUNG FISIP UNIVERSITAS MUHAMMADIYAH SIDOARJO - Farah Nuriyana; Warsito Warsito; Bambang Suprapto (Universitas Islam Malang, 2020)
Structure Planning is intending to produce a stable, strong, durable structure and to fulfill thedesirable purposes.The more development of era and technology improvement,the developmentproject also following the current of development by searching some various alternative planning,for example by using the alternative of composite structure method. Composite structure is amaterial which formed by two or more materials which different as physically and character, suchas concrete and steel.That combination will produce a stronger profile design, light, and moreeconomic rather than non-composite structure.This lecture building of FISIP is located in Campus1 of Sidoarjo Muhammadiyah University, which has seven floors with width of the building is16,5m, the length is 24,5m, the height is 31,75m, and be included in earthquake risk zone 3. In thislast assignment writing that is re-planning by using alternative of composite method and countingprocess by using StaadPro application with 2D portal modeling.The last result which is obtained the plate thickness 12,5cm with main reinforcement 10-125 and reinforcement for 10-150; thesecondary beam using steel profile WF300.150.6,5.9, WF250.126.6.9;the main beam using steelprofile WF500.200.10.16;the column using steel profile WF400.400.15.15;and foundationplanning is using piling foundation by using 50cm diameter and 50m depth. Keyword : Structure Planning, Composite Structure, Lecture Building.